background image

Provided that

[

f

]=[

g

]

we have

/

h

f

iX , X

[

f

]

Y , X

[

g

]

Y , Y 

/

h

g

iX

and consequently

h

f

iX

=

h

g

iX

for every

X 2

F

(

A

)

,

Y 2

F

(

B

)

because a set of lters is separable, thus

h

f

i

=

h

g

i

.

Proposition 6.12.

h

f

i

0

F

(

Src

f

)

= 0

F

(

Dst

f

)

for every funcoid

f

.

Proof.

/

h

f

i

0

F

(

Src

f

)

,

0

F

(

Src

f

)

/

h

f

¡

1

iY ,

0

, Y 

/ 0

F

(

Dst

f

)

. Thus

h

f

i

0

F

(

Src

f

)

= 0

F

(

Dst

f

)

by

separability of lters.

Proposition 6.13.

h

f

i

(

I t J

) =

h

f

iI t h

f

iJ

for every funcoid

f

and

I

;

J 2

F

(

Src

f

)

.

Proof.

?

h

f

i

(

I t J

) =

fY 2

F

j Y 

/

h

f

i

(

I t J

)

g

=

fY 2

F

j I t J 

/

h

f

¡

1

iY g

=

fY 2

F

j I 

/

h

f

¡

1

iY _ J 

/

h

f

¡

1

iY g

=

fY 2

F

j Y 

/

h

f

iI _ Y 

/

h

f

iJ g

=

fY 2

F

j Y 

/

h

f

iI t h

f

iJ g

=

?

(

h

f

iI t h

f

iJ

)

:

Thus

h

f

i

(

I t J

) =

h

f

iI t h

f

iJ

because

F

(

Dst

f

)

is separable.

Proposition 6.14.

For every

f

2

FCD

(

A

;

B

)

for every sets

A

and

B

we have:

1.

K

[

f

]

I t J , K

[

f

]

I _ K

[

f

]

J

for every

I

;

J 2

F

(

B

)

,

K 2

F

(

A

)

.

2.

I t J

[

f

]

K , I

[

f

]

K _ J

[

f

]

K

for every

I

;

J 2

F

(

A

)

,

K 2

F

(

B

)

.

Proof.

1.

K

[

f

]

I t J ,

(

I t J

)

u h

f

iK

=

/ 0

F

(

B

)

, I u h

f

iK

=

/ 0

F

(

B

)

_ J u h

f

iK

=

/ 0

F

(

B

)

, K

[

f

]

I _

K

[

f

]

J

.

2. Similar.

6.2.1 Composition of funcoids

Denition 6.15.

Funcoids

f

and

g

are

composable

when Dst

f

=

Src

g

.

Denition 6.16.

Composition

of composable funcoids is dened by the formula

(

B

;

C

;

2

;

2

)

(

A

;

B

;

1

;

1

) = (

A

;

C

;

2

1

;

1

2

)

:

Proposition 6.17.

If

f

,

g

are composable funcoids then

g

f

is a funcoid.

Proof.

Let

f

= (

A

;

B

;

1

;

1

)

,

g

= (

B

;

C

;

2

;

2

)

. For every

X 2

F

(

A

)

,

Y 2

F

(

C

)

we have

/ (

2

1

)

X , Y 

/

2

1

X ,

1

/

2

Y , X 

/

1

2

Y , X 

/ (

1

2

)

Y

:

So

(

A

;

C

;

2

1

;

1

2

)

is a funcoid.

Obvious 6.18.

h

g

f

i

=

h

g

i  h

f

i

for every composable funcoids

f

and

g

.

Proposition 6.19.

(

h

g

)

f

=

h

(

g

f

)

for every composable funcoids

f

,

g

,

h

.

Proof.

h

(

h

g

)

f

i

=

h

h

g

ih

f

i

= (

h

h

ih

g

i

)

h

f

i

=

h

h

i

(

h

g

ih

f

i

) =

h

h

ih

g

f

i

=

h

h

(

g

f

)

i

.

Theorem 6.20.

(

g

f

)

¡

1

=

f

¡

1

g

¡

1

for every composable funcoids

f

and

g

.

Proof.

h

(

g

f

)

¡

1

i

=

h

f

¡

1

i  h

g

¡

1

i

=

h

f

¡

1

g

¡

1

i

.

6.2 Basic definitions

97